Bipolar Plasma Membrane Distribution of Phosphoinositides and Their Requirement for Auxin-Mediated Cell Polarity and Patterning in Arabidopsis . Issue 5 (29th May 2014) - Tejos, Ricardo; Sauer, Michael; Vanneste, Steffen; Palacios-Gomez, Miriam; Li, Hongjiang; Heilmann, Mareike; van Wijk, Ringo; Vermeer, Joop E.M.; Heilmann, Ingo; Munnik, Teun; Friml, Jiří
Abstract : This work shows that PtdIns4P and PtdIns(4, 5)P2, together with PIP5K1 and PIP5K2, mark the apical and basal polar domains in the root epidermis, embryos, and lateral root primordia. The findings support the idea that a regulatory loop involving plasma membrane–associated phosphoinositides modulates apical–basal PIN polarity via crosstalk between auxin signaling and the PIN polarizing machinery. Abstract: Cell polarity manifested by asymmetric distribution of cargoes, such as receptors and transporters, within the plasma membrane (PM ) is crucial for essential functions in multicellular organisms. In plants, cell polarity (re)establishment is intimately linked to patterning processes. Despite the importance of cell polarity, its underlying mechanisms are still largely unknown, including the definition and distinctiveness of the polar domains within the PM . Here, we show in Arabidopsis thaliana that the signaling membrane components, the phosphoinositides phosphatidylinositol 4-phosphate (PtdIns4P ) and phosphatidylinositol 4, 5-bisphosphate [PtdIns(4, 5)P2 ] as well as PtdIns4P 5-kinases mediating their interconversion, are specifically enriched at apical and basal polar plasma membrane domains. The PtdIns4P 5-kinases PIP5K1 and PIP5K2 are redundantly required for polar localization of specifically apical and basal cargoes, such as PIN-FORMED transporters for the plant hormone auxin. As a consequence of the polarity defects, instructive auxin gradients as well as embryonic and postembryonic patterning are severely compromised. Furthermore, auxin itself regulates PIP5K transcription and PtdIns4P and PtdIns(4, 5)P2 levels, in particular their association with polar PM domains. Our results provide insight into the polar domain–delineating mechanisms in plant cells that depend on apical and basal distribution of membrane lipids and are essential for embryonic and postembryonic patterning.